2015
DOI: 10.1039/c5ra01416f
|View full text |Cite
|
Sign up to set email alerts
|

Dithieno[3,2-a:2′,3′-c]phenazine-based chemical probe for anions: a spectroscopic study of binding

Abstract: The synthesis and binding studies of N,N′-(2,5-bis(4-(tert-butyl)phenyl)dithieno[3,2-a:2′,3′-c]phenazine-9,10-diyl)bis(4-methylbenzenesulfonamide) (1) are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A dithieno[3,2‐ a :2′,3′‐ c ]phenazine‐based bis(sulfonamide) receptor 24 (Figure ) for anion detection has been reported by Kaafarani and co‐workers . Anion binding studies using fluorescence and 1 H NMR titration experiments revealed strong binding of 24 with cyanide, carboxylate (acetate and benzoate), and dihydrogenphosphate.…”
Section: Quinoxaline‐based Anion Sensorsmentioning
confidence: 77%
See 1 more Smart Citation
“…A dithieno[3,2‐ a :2′,3′‐ c ]phenazine‐based bis(sulfonamide) receptor 24 (Figure ) for anion detection has been reported by Kaafarani and co‐workers . Anion binding studies using fluorescence and 1 H NMR titration experiments revealed strong binding of 24 with cyanide, carboxylate (acetate and benzoate), and dihydrogenphosphate.…”
Section: Quinoxaline‐based Anion Sensorsmentioning
confidence: 77%
“…Ad ithieno[3,2-a:2',3'-c]phenazine-based bis(sulfonamide) receptor 24 (Figure18) for anion detection has been reportedb y Kaafarani and co-workers. [48] Anion binding studies using fluorescencea nd 1 HNMR titration experiments revealed strong binding of 24 with cyanide,c arboxylate (acetate and benzoate), and dihydrogenphosphate. Fluorescence titration of 24 (CHCl 3 )w ith any of these anions resulted in an enhancement of the emission intensity of the probe with concomitant blue shift from 620 to 560 nm.…”
Section: Quinoxaline Sulfonamidesmentioning
confidence: 99%
“…29 Reported in this publication, dithienophenazines (Scheme 1) represent a wide class of novel organic π-conjugated compounds with the same core structure as shown in Scheme 1, but various positions of heteroatoms. [31][32][33][34][35][36][37][38][39] These compounds attracted considerable interest as potential materials for diverse applications in organic electronics, such as organic light-emitting diodes (OLEDs) 31 as well as pendant groups in donor-acceptor polymers for solar cell application [32][33][34] in dye-sensitized solar cells, [35][36][37] and in anion probes. 38 This aromatic system with sp 2 -hybridized nitrogen atoms might be capable of formation of C-H⋯N hydrogen bonds, and these had been shown to assist molecular self-assembly and increase charge mobility in thin films.…”
Section: Introductionmentioning
confidence: 99%
“…DTPhz has been exploited as an acceptor unit in DA copolymers employed in solar cells, 31,32 as a light absorber in dye-sensitized solar cells, 33 and as an anion probe. 34 TCNQ and its derivative forms are among the most widely used A units in the DA cocrystal literature. 1,4,8,12,22,23,25,29,35,36 Details of the synthesis and characterization of DTPhz are provided in the Supporting Information (SI); TCNQ was used as received.…”
mentioning
confidence: 99%
“…The DA cocrystal of interest in this study was synthesized by combining dithieno­[3,2- a :2′,3′- c ]­phenazine (DTPhz) as the D moiety and 7,7,8,8-tetracyanoquinodimethane (TCNQ) as the A moiety (Figure ). DTPhz has been exploited as an acceptor unit in DA copolymers employed in solar cells, , as a light absorber in dye-sensitized solar cells, and as an anion probe . TCNQ and its derivative forms are among the most widely used A units in the DA cocrystal literature. ,,,,,,,,, Details of the synthesis and characterization of DTPhz are provided in the Supporting Information (SI); TCNQ was used as received.…”
mentioning
confidence: 99%